A transient coking model of hydrocarbon pyrolysis in hot pipe based on RPM analogy. (5th April 2023) - Li, Haowen; Wang, Xiaohan; Li, Tao; Song, Qianshi; Yang, Zixin; Zhang, Wei; Zhang, Jie; Wang, Zhenfeng
Graphical abstract: Highlights: A transient coking model C-RPM was constructed to predict the time-dependent cumulative behavior of tube wall coking. The coking process of coke particles is analogous to the expansion and overlapping process of pores based on random pore model. A calculation procedure in view of error transfer based on surface kinetic calculations combined with the C-RPM model was proposed to determine coking reaction rate. The coking curve is controlled by pseudo-structure function and the surface reaction function. The coking critical state with particle diameter d crit and coke mass m crit is most sensitive to coking curve. Abstract: In regenerative cooling channel, predicting the time-dependent cumulative behavior of wall coking associated with endothermic hydrocarbon fuel pyrolysis is critical which is deficient now. The growth of coke is similar to the gasification of solid in the phenomenon by observing the morphology evolution. In this study, a transient coking model C-RPM, which consists of pseudo-structure function and surface reaction function two parts, was constructed on the basis of random pore model (RPM) for the initial presence of catalytic coking process. After scaling in time dimension, a good agreement with the unsteady-state coking experiments of n -heptane (NC7) and methylcyclohexane (MCH) was achieved. Sensitivity analysis was performed and results showed the critical particle size d crit and coke mass m crit were the most important parameters affecting the coking curve. The coking space after particle fusion ψ ( t ) determines the mode of coke weight gain curve. A multi-stage periodic coking process may exist by inference.